Fall Prevention: Lifestyle Factors and Fall Risk - Jennifer Hillan (EDIS)
There are many things that may cause you to fall, and you can change several of them. This document includes some easy changes you can make to decrease your risk of falling. This document is FCS2230, one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: April 2005.